BIBLIOMETRIC ANALYSIS OF HALAL LIFESTYLE MARKETING MIX FOR THE PERIOD 2020-2025 WITH VOS VIEWER - Mastika Sari Harahap; Rosnani Siregar; Utari Evy Cahyani (Nurul Jadid University, 2025)
This study aims to explore research trends on the marketing mix in the context of the halal lifestyle using bibliometric analysis. Using the VOSviewer software, this research analyzes 997 documents published between 2020 and 2025 related to this topic. The findings indicate that the topic of the halal lifestyle marketing mix is gaining increasing attention from researchers, with journal publications being the primary source of information. Network visualization reveals five main clusters related to marketing aspects, religiosity, purchasing decisions, halal supply chains, and digital marketing. This study provides insights into research trends and the future direction of halal product marketing strategies.